A moment on the edge : 100 years of crime stories by women - George, Elizabeth, 1949-. (HarperCollins, 2005)
New York Times bestselling author Elizabeth George serves up a century's worth of superb crime fiction penned by women. This veritable all-star team delivers tales of dark deeds that will keep you reading long into the night. Included are these works: "A Jury of Her Peers" by Susan Glaspell The Summer of People" by Shirley Jackson "The Irony of Hate" by Ruth Rendell "Country Lovers" by Nadine Gordimer "Wild Mustard" by Marcia Muller "Murder-Two" by Joyce Carol Oates A Moment on the Edge is a rare treat not only for fans of crime fiction but also for anyone who appreciates a skillfully written, deftly told story.